Hard carbon negative electrode material, preparation method thereof, negative electrode sheet and sodium ion battery

CN121134732BActive Publication Date: 2026-10-27深圳为方能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511315598.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2026-10-27
Estimated Expiration
2045-09-15

AI Technical Summary

Technical Problem

[0007]本申请的目的在于提供一种硬炭负极材料及其制备方法、负极片和钠离子电池,旨在解决现有硬炭负极材料在制备过程中易形成熔融态和发泡的问题

Benefits of technology

本申请提供的硬炭负极材料的制备方法通过以高分子物质基和化石燃料基硬碳为前驱体,并在前驱体材料中加入发泡辅助剂,采用热处理固化和高温碳化的处理方式,最大限度降低材料的熔融和发泡情况,提高材料交联度,以达到提供高分子物质基和化石燃料基硬碳以更好的孔隙结构及更高容量、更高压实的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121134732B_ABST
    Figure CN121134732B_ABST
Patent Text Reader

Abstract

The application provides a hard carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a sodium ion battery, and relates to the technical field of new energy. The preparation method of the hard carbon negative electrode material provided by the application takes a high polymer substance-based and fossil fuel-based hard carbon as a precursor, adds a foaming auxiliary agent in the precursor material, adopts a heat treatment solidification and high-temperature carbonization treatment mode, maximally reduces the melting and foaming of the material, and improves the crosslinking degree of the material, so that the high polymer substance-based and fossil fuel-based hard carbon has a better pore structure and higher capacity and compaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, and in particular to a hard carbon anode material and its preparation method, an anode sheet, and a sodium-ion battery. Background Technology

[0002] Sodium-ion batteries, due to their excellent fast-charging performance and ultra-high capacity retention at -40℃, have become a powerful complement to lithium-ion batteries in the electric vehicle field. However, sodium-ion batteries have a significant shortcoming in energy density, limiting their application and market share expansion in the electric vehicle sector. Existing technologies for anode-less sodium-ion batteries have greatly improved the energy density of individual cells, but at the expense of cycle performance and safety characteristics. To improve the energy density of sodium-ion batteries while ensuring their cycle stability and safety performance, and to narrow the energy density gap between sodium-ion and lithium-ion batteries, developing high-compaction, high-capacity anode materials is a crucial step.

[0003] Hard carbon is considered the most promising commercial anode material for sodium-ion batteries due to its high capacity and low cost. Thanks to rapid industrialization, some challenges associated with hard carbon anodes have been largely resolved, such as the low initial coulombic efficiency. Currently, the initial efficiency of hard carbon has increased from 75%–80% to 90% or even higher, significantly improving the areal capacity of sodium-ion anode sheets and the specific capacity of the battery. However, compared to lithium-ion graphite anodes, the compaction density of hard carbon anode sheets is much lower than that of graphite anode sheets.

[0004] Currently, biomass-based hard carbon has become the mainstream in the hard carbon industry due to its moderate processing and performance. However, its compaction density and specific capacity are limited by the structure of the biomass raw materials and cannot be further improved. In addition, from a long-term perspective, the seasonality and uniformity of biomass-based hard carbon, as well as the high cost of acid washing and the environmental pollution of the acid washing process, cause biomass-based hard carbon to lose its natural low-cost advantage. Furthermore, due to the superior performance of coconut shell-based hard carbon among biomass-based hard carbons, the supply of coconut shells is insufficient, and the price has been rising continuously. This may become a major pain point for the industrialization of biomass hard carbon anode materials in the future.

[0005] Therefore, in the current development of the hard carbon industry, related research and development work is focusing on various types of precursor materials. One type is high-molecular-weight long-chain precursors, including starch, sugars, resins, etc. Another type is fossil fuel precursors, such as pitch and petroleum coke. These precursors not only have low raw material costs and extremely high purity, but their supply is also unaffected by seasons or the environment, making them a highly industrialized choice for hard carbon anodes. In addition, when high-molecular-weight and fossil fuel-based hard carbons are used as anode materials for sodium-ion batteries, they exhibit high compaction and high capacity characteristics, which provides a direction for improving the energy density of sodium-ion batteries.

[0006] However, the preparation of polymer-based and fossil fuel-based hard carbons faces significant limitations. Specifically, during high-temperature pyrolysis and other processing steps, these two types of hard carbon materials inevitably form a molten state. This leads to fossil fuel-based precursors readily forming soft carbon, while long-chain polymer precursors easily transform into a disordered liquid state. Furthermore, the high-temperature heating process generates gases (such as CO2 and CH4), and excessive accumulation of these gases causes foaming and other negative effects, resulting in severe material loss and extremely low yield during preparation. In summary, the tendency to form a molten state and foaming during preparation poses a major obstacle to the industrialization of polymer-based and fossil fuel-based hard carbons. Summary of the Invention

[0007] The purpose of this application is to provide a hard carbon anode material and its preparation method, anode sheet and sodium-ion battery, aiming to solve the problem that existing hard carbon anode materials are prone to forming a molten state and foaming during the preparation process.

[0008] To achieve the above objectives, this application provides a method for preparing a hard carbon anode material, comprising: The precursor and foaming aid were mixed and then ethanol was added to obtain a mixture; The mixture is then subjected to heat treatment to solidify it, resulting in a mixture powder. The mixture powder is subjected to high-temperature carbonization to obtain the hard carbon anode material.

[0009] In some embodiments, the mass ratio of the precursor to the foaming agent is (3~10):1.

[0010] In some embodiments, the ratio of the sum of the volumes of the precursor and the foaming agent to the volume of the ethanol is (1~16):1.

[0011] In some embodiments, the foaming agent includes acidic substances or natural polymeric substances; The acidic substances include at least one of phosphoric acid, citric acid, oxalic acid, acetic acid, and tartaric acid. The natural polymeric substances include at least one of the following: chitin, chitosan, urea, sodium alginate, pectin, and cellulose.

[0012] In some embodiments, the heat treatment curing temperature is 160~200℃, the time is 1~3 h, and the heating rate is 1~2℃ / min.

[0013] In some embodiments, the high-temperature carbonization temperature is 1100℃~1600℃, the time is 2h~4h, and the heating rate is 2~5℃ / min; And / or, the high-temperature carbonization is carried out in an argon atmosphere at a gas flow rate of 200-250 mL / min.

[0014] In some embodiments, the precursor is selected from polymer-based precursors and fossil fuel-based precursors; The polymer-based precursor includes any one of liquid phenolic resin, polyacrylonitrile, starch, sucrose, and industrial sugar. The fossil fuel-based precursors include any one of bitumen, petroleum coke, and anthracite.

[0015] In some embodiments, the hard carbon anode material is crushed and sieved to obtain the finished hard carbon anode material.

[0016] In some embodiments, the pulverization method includes any one of ball milling, air jet milling, and ultrasonic milling.

[0017] In some embodiments, the ball milling process parameters are 400~1000 rpm for 2~24 hours.

[0018] In some embodiments, the parameters of the airflow pulverization process are an airflow velocity of 300-500 m / s and a compressed gas pressure of 0.4-1.2 MPa.

[0019] In some embodiments, the ultrasonic pulverizing process parameters are a working frequency of 20-25 kHz and a working capacity of 1500 mL.

[0020] This application also provides a hard carbon anode material, which is prepared by the above-described method for preparing hard carbon anode materials; Preferably, the particle size D50 of the hard carbon anode material is in the range of 4~6 μm; Preferably, the particle size distribution K90 of the hard carbon anode material is in the range of 1.6~2.0; Preferably, the pore volume of the hard carbon anode material is 0.05 cm³. 3 / g~0.07cm 3 / g; Preferably, the pore size of the hard carbon anode material is 1.4~2.0 nm; Preferably, the true density of the hard carbon anode material is 1.0 to 1.5.

[0021] This application also provides a negative electrode sheet, the raw material of which includes the above-mentioned hard carbon negative electrode material.

[0022] This application also provides a sodium-ion battery, including the aforementioned negative electrode.

[0023] Compared with the prior art, the beneficial effects of this application include: The preparation method of the hard carbon anode material provided in this application uses polymer-based and fossil fuel-based hard carbon as precursors, adds foaming aids to the precursor materials, and adopts heat treatment curing and high-temperature carbonization to minimize the melting and foaming of the material and improve the cross-linking degree of the material, so as to provide polymer-based and fossil fuel-based hard carbon with better pore structure, higher capacity and higher compaction.

[0024] During the crosslinking and curing reactions, the oxygen-containing groups in the foaming aid can react with both types of precursors, increasing the melting temperature of the material, reducing the foaming rate, and improving the material yield. Furthermore, the foaming aid can introduce oxygen-containing functional groups, primarily carbonyl groups, maintaining a large interlayer spacing during subsequent high-temperature carbonization. Ethanol acts as a reactant to accelerate the material curing process and can also vaporize between the crosslinking matrices, thereby creating micropores in the material. By controlling the amount of ethanol used, the microporous structure of the material can be precisely controlled. During the subsequent high-temperature carbonization process, the micropores generated by ethanol evaporation can further form abundant closed pores, thereby improving the material's capacity and initial efficiency.

[0025] The preparation method of hard carbon anode material provided in this application uses mature industrial precursors that are low in price, high in purity, and require no acid washing. Relying on a mature industrial production system, the annual production capacity of precursors is stable at over 100,000 tons, ensuring the continuity and batch consistency of raw material supply. Compared to biomass-based materials, this avoids quality problems caused by seasonal raw material fluctuations. The yield of polymer-based and fossil fuel-based hard carbon can reach 40-50%, far exceeding the 20-28% for biomass-based hard carbon, significantly improving output efficiency per unit time and reducing the overall manufacturing cost per unit product. The use of an acid-free production process avoids the use of polluting chemicals such as strong acids and alkalis, significantly reducing the environmental adaptability requirements of the production site and the difficulty of environmental impact assessment approval, achieving the goal of clean production.

[0026] The hard carbon anode material provided in this application can adjust the pore structure of polymer-based and fossil fuel-based hard carbon by controlling process parameters, reducing the proportion of meaningless pores (pore size ≤ 0.7 nm, pores that cannot store sodium), improving the pore utilization rate of the material, and thus improving the true density and compaction density of the material; by introducing an auxiliary foaming agent to regulate the pyrolysis kinetics of the precursor, the molten agglomeration and foaming phenomena are effectively suppressed; and an innovative in-situ pore-forming strategy is adopted to construct abundant effective pores in the material, significantly improving the specific capacity and first coulombic efficiency of the material, and achieving synergistic optimization of electrochemical performance.

[0027] The negative electrode provided in this application improves the true density and particle size distribution of the hard carbon negative electrode material, thereby increasing the compaction density of the material and the electrode. The resulting high surface capacity electrode has a first discharge specific capacity of over 380 mAh / g, a first efficiency of over 92%, and a capacity retention rate of over 79% at a high charge-discharge rate of 10C. Attached Figure Description

[0028] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0029] Figure 1 This is a schematic flowchart of the preparation method of the hard carbon anode material of this application; Figure 2 The charge-discharge curves of the battery obtained by assembling the hard carbon negative electrode material of Example 1 are shown. Figure 3 The diagram shows the rate performance of the battery obtained by assembling the hard carbon anode material of Example 1. Detailed Implementation

[0030] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0031] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0032] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0033] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.

[0034] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.

[0035] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0036] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0037] This application provides a method for preparing a hard carbon anode material. Please refer to [link / reference]. Figure 1 ,include: S100: After mixing the precursor and the foaming aid, ethanol is added to obtain a mixture; S200: The mixture is heat-treated and cured to obtain a mixture powder; S300: The mixture powder is subjected to high-temperature carbonization to obtain hard carbon anode material.

[0038] In some embodiments, the mass ratio of the precursor to the foaming agent in step S100 is (3~10):1, for example, it can be any value between 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or (3~10):1.

[0039] In some embodiments, the ratio of the sum of the volumes of the precursor and the foaming aid in step S100 to the volume of the ethanol is (1~16):1, for example, it can be any ratio between 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1 or (1~16):1.

[0040] In some embodiments, the foaming aid in step S100 includes acidic substances or natural polymeric substances; The acidic substances include at least one of phosphoric acid, citric acid, oxalic acid, acetic acid, and tartaric acid. The natural polymeric substances include at least one of the following: chitin, chitosan, urea, sodium alginate, pectin, and cellulose.

[0041] In some embodiments, the precursor in step S100 is selected from polymer-based precursors and fossil fuel-based precursors; The polymer-based precursor includes any one of liquid phenolic resin, polyacrylonitrile, starch, sucrose, and industrial sugar. The fossil fuel-based precursors include any one of bitumen, petroleum coke, and anthracite.

[0042] In some embodiments, the heat treatment curing temperature in step S200 is 160~200℃, for example, it can be any value between 160℃, 170℃, 180℃, 190℃, 200℃ or 160~200℃, the time is 1~3 h, for example, it can be any value between 1h, 2h, 3h or 1~3 h, and the heating rate is 1~2℃ / min, for example, it can be any value between 1℃ / min, 1.5℃ / min, 2℃ / min or 1~2℃ / min.

[0043] In some embodiments, the high-temperature carbonization temperature in step S300 is 1100℃~1600℃, for example, it can be any value between 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃ or 1100℃~1600℃, the time is 2h~4h, for example, it can be any value between 2h, 3h, 4h or 2h~4h, and the heating rate is 2~5℃ / min, for example, it can be any value between 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min or 2~5℃ / min.

[0044] In some embodiments, the high-temperature carbonization in step S300 is carried out in an argon atmosphere with a gas flow rate of 200-250 mL / min, for example, it can be any value between 200 mL / min, 210 mL / min, 220 mL / min, 230 mL / min, 240 mL / min, 250 mL / min or 200-250 mL / min.

[0045] In some embodiments, the hard carbon anode material in step S300 is crushed and sieved to obtain the finished hard carbon anode material.

[0046] In some embodiments, the pulverization method includes any one of ball milling, air jet milling, and ultrasonic milling.

[0047] In some embodiments, the ball milling process parameters are 400~1000 rpm for 2~24 hours.

[0048] In some embodiments, the parameters of the airflow pulverization process are an airflow velocity of 300-500 m / s and a compressed gas pressure of 0.4-1.2 MPa.

[0049] In some embodiments, the ultrasonic pulverizing process parameters are a working frequency of 20-25 kHz and a working capacity of 1500 mL.

[0050] This application also provides a hard carbon anode material, which is prepared by the above-described method for preparing hard carbon anode materials; Preferably, the particle size D50 of the hard carbon anode material is in the range of 4~6 μm; Preferably, the particle size distribution K90 of the hard carbon anode material is in the range of 1.6~2.0; Preferably, the pore volume of the hard carbon anode material is 0.05 cm³. 3 / g~0.07cm 3 / g; Preferably, the pore size of the hard carbon anode material is 1.4~2.0 nm; Preferably, the true density of the hard carbon anode material is 1.0 to 1.5.

[0051] This application also provides a negative electrode sheet, the raw material of which includes the above-mentioned hard carbon negative electrode material.

[0052] This application also provides a sodium-ion battery, including the aforementioned negative electrode.

[0053] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0054] Example 1 Example 1 provides a hard carbon anode material, the preparation method of which includes the following steps: (1) Mix fossil fuel-based precursor pitch and foaming agent oxalic acid in a mortar at a mass ratio of 5:1. Then add ethanol at a certain volume ratio. The volume ratio of the sum of the volumes of the precursor and the foaming agent to the volume of ethanol is 10:1. Stir at room temperature for 2 hours to mix evenly to obtain a mixture. (2) The mixture was transferred to a high pressure vessel and subjected to heat treatment curing reaction at a temperature of 180 °C for 2 hours. The heating rate of the heat treatment curing reaction was 2 °C / min. After solvent heat treatment curing, the powder was repeatedly washed with deionized water three times and then dried in an oven at a temperature of 80 °C for 12 hours to obtain the mixture powder. (3) The cleaned mixture powder was placed in a tube furnace and subjected to high-temperature carbonization in an argon atmosphere. The gas flow rate was 200 mL / min, the high-temperature carbonization temperature was 1400 °C, the high-temperature carbonization time was 2 h, and the heating rate was 2 °C / min, to obtain the hard carbon anode material of Example 1. Example 1 also provides a negative electrode sheet, the preparation method of which includes the following steps: 1. The hard carbon anode material of Example 1 is passed through an airflow pulverizer. By controlling the airflow speed and classification of the airflow pulverizer, the particle size and particle size distribution of the material are adjusted. Finally, it is passed through a 300-mesh sieve, and the D50 of the hard carbon anode material is adjusted to 4~6µm, and K90=(D90-D10) / D50 is 1.6-2.0. 2. After the particle size of the hard carbon microparticles, conductive agent (SP) and binder (CMC, SBR) are adjusted, they are mixed with a certain amount of deionized water in a mass ratio of 94:2:2:2 and then coated onto the current collector to obtain the sodium-ion battery negative electrode sheet of Example 1.

[0055] Example 2 The only difference between Example 2 and Example 1 is that step (1) increases the amount of ethanol, and the volume ratio of the sum of the volumes of the precursor and the foaming agent to the volume of ethanol is 5:1. The remaining steps are the same as in Example 1.

[0056] Example 3 The only difference between Example 3 and Example 1 is that the amount of ethanol used in step (1) is reduced, and the volume ratio of the sum of the volumes of the precursor and the foaming agent to the volume of ethanol is 15:1. The remaining steps are the same as in Example 1.

[0057] Example 4 The only difference between Example 4 and Example 1 is that in step (1), the fossil fuel-based precursor pitch is replaced with liquid phenolic resin, and the rest of the steps are the same as in Example 1.

[0058] Example 5 The only difference between Example 5 and Example 4 is that in step (1), the foaming agent oxalic acid is replaced with chitosan, and the rest of the steps are the same as in Example 4.

[0059] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the foaming agent oxalic acid is not added in step (1), and the rest of the steps are the same as in Example 1.

[0060] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that in step (1), ethanol is replaced with water, and the rest of the steps are the same as in Example 1.

[0061] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the temperature of high-temperature carbonization in step (3) is 1000°C, and the other steps are the same as in Example 1.

[0062] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the temperature of high-temperature carbonization in step (3) is 1700°C, and the other steps are the same as in Example 1.

[0063] Comparative Example 5 The only difference between Comparative Example 5 and Example 1 is that the K90 of the hard carbon anode material in Comparative Example 5 is adjusted to 2.3-2.5, and the other steps are the same as in Example 1.

[0064] Comparative Example 6 The only difference between Comparative Example 6 and Example 1 is that the D50 of the hard carbon anode material in Comparative Example 6 is adjusted to 7~9µm and the K90 is adjusted to 1.1-1.3. The remaining steps are the same as in Example 1.

[0065] The parameters of the hard carbon anode materials in each embodiment and comparative example are shown in Table 1.

[0066] Table 1. Parameters of hard carbon anode materials in each embodiment and comparative example.

[0067] The electrochemical performance of each example and comparative example was tested using a half-cell test method. Sodium sheets were used as the positive electrode, and copper foil and aluminum foil were used as the negative and positive current collectors, respectively. Celgard 2300 type separators were used, and 1 M NaPF6 in EC:DMC = 1:1 electrolyte (produced by Nanjing Mojies Technology Co., Ltd.) was used as the electrolyte. Button batteries were assembled in an argon-glove drying oven (moisture content controlled below <15 ppm). Batteries prepared using the above basic conditions were tested using a computer-controlled testing instrument. The charging current was 0.1C, the discharging current was 0.1C, and the charge / discharge voltage range was 0~2.0V. The charge / discharge test results of the battery prepared with the hard carbon negative electrode material in Example 1 are as follows: Figure 2 As shown, the rate performance is as follows Figure 3 As shown.

[0068] Using Examples 1-5 and Comparative Examples 1-6 as samples, the batteries assembled from the aforementioned samples were subjected to electrochemical performance testing. The testing conditions were: current density of 30 mA / g and voltage range of 0~2 V. The test results are shown in Table 2.

[0069] Table 2 Test results for each embodiment and comparative example

[0070] According to the data in Table 2, Examples 1 to 3 used different amounts of ethanol to reasonably control the pore size and pore volume of the material, resulting in materials with different capacities and initial performance. Specifically, in Example 2, increasing the amount of ethanol compared to Example 1 increased the pore size, causing the pores to not completely form closed pores during carbonization, resulting in more open pores, lower initial performance, and reduced material true density. In Example 3, decreasing the amount of ethanol compared to Example 1 led to insufficient pore formation, smaller pores, and insufficient closed-pore volume for sodium storage, thus reducing capacity. The hard carbon anode materials of Examples 4 to 5 were prepared using different precursors or different foaming agents. The electrochemical performance of the resulting batteries was comparable to that of Example 1 and higher than that of the comparative example, indicating that the method of this application is applicable to different precursors and foaming agents.

[0071] Comparative Example 1, without the addition of foaming aids, resulted in insufficient cross-linking of the material during preparation, leading to low yield and capacity of the hard carbon anode material. Comparative Example 2, using water instead of ethanol, produced a hard carbon anode material with larger pore sizes and smaller overall volume, unsuitable for sodium storage, thus reducing its capacity and initial efficiency. Comparative Examples 3 and 4 demonstrate that excessively high or low carbonization temperatures affect the performance of hard carbon anode materials. Specifically, excessively high temperatures lead to smaller interlayer spacing, directly affecting the material's specific capacity; excessively low temperatures result in incomplete conversion of open-cell to closed-cell processes, leading to more open cells and reduced initial efficiency. The different particle size distributions of the hard carbon anode materials in Comparative Examples 5 and 6 affect the electrode compaction density, directly impacting the cell's energy density and capacity.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0073] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a hard carbon anode material, characterized in that, include: The precursor and foaming aid were mixed and then ethanol was added to obtain a mixture; The mixture is then subjected to heat treatment to solidify it, resulting in a mixture powder. The mixture powder is subjected to high-temperature carbonization treatment to obtain the hard carbon anode material; The precursor is selected from polymer-based precursors and fossil fuel-based precursors; The polymer-based precursor includes any one of liquid phenolic resin and polyacrylonitrile; The fossil fuel-based precursors include any one of bitumen, petroleum coke, and anthracite. The foaming aids include acidic substances or natural polymeric substances; The acidic substances include at least one of phosphoric acid, citric acid, oxalic acid, acetic acid, and tartaric acid. The natural polymeric substances include at least one of the following: chitin, chitosan, sodium alginate, pectin, and cellulose; The mass ratio of the precursor to the foaming agent is (3~10):1; The ratio of the sum of the volumes of the precursor and the foaming agent to the volume of the ethanol is (1~16):

1.

2. The method for preparing the hard carbon anode material according to claim 1, characterized in that, The heat treatment curing temperature is 160~200℃, the time is 1~3 h, and the heating rate is 1~2℃ / min.

3. The method for preparing the hard carbon anode material according to claim 1, characterized in that, The high-temperature carbonization temperature is 1100℃~1600℃, the time is 2h~4h, and the heating rate is 2~5℃ / min; And / or, the high-temperature carbonization is carried out in an argon atmosphere at a gas flow rate of 200-250 mL / min.

4. A hard carbon anode material, characterized in that, It is prepared by the method for preparing hard carbon anode material according to any one of claims 1 to 3.

5. The hard carbon anode material according to claim 4, characterized in that, The particle size D50 of the hard carbon anode material ranges from 4 to 6 µm.

6. The hard carbon anode material according to claim 4, characterized in that, The particle size distribution K90 of the hard carbon anode material ranges from 1.6 to 2.

0.

7. The hard carbon anode material according to claim 4, characterized in that, The pore volume of the hard carbon anode material is 0.05 cm³. 3 / g~0.07cm 3 / g.

8. The hard carbon anode material according to claim 4, characterized in that, The hard carbon anode material has a pore size of 1.4~2.0 nm.

9. The hard carbon anode material according to claim 4, characterized in that, The true density of the hard carbon anode material is 1.0~1.

5.

10. A negative electrode sheet, characterized in that, Its raw materials include the hard carbon anode material as described in any one of claims 4 to 9.

11. A sodium-ion battery, characterized in that, Includes the negative electrode sheet as described in claim 10.

Citation Information

Patent Citations

  • Hard carbon material, preparation method thereof and negative pole piece

    CN115818619A

  • Preparation method of sodium ion battery negative electrode hard carbon material based on skeleton particle filling

    CN120534955A